Supervised physical exercise improves clinical, anthropometric and biochemical parameters in adult cystic fibrosis patients: A 2‐year evaluation. (30th April 2018) - Elce, Ausilia; Nigro, Ersilia; Gelzo, Monica; Iacotucci, Paola; Carnovale, Vincenzo; Liguori, Renato; Izzo, Viviana; Corso, Gaetano; Castaldo, Giuseppe; Daniele, Aurora; Zarrilli, Federica
Abstract: Objective: Cystic fibrosis (CF) is the most common inherited, life limiting condition among Caucasians. No healing therapy is currently available for patients with CF. The aim of the study was to define clinical, anthropometric and biochemical effects of regular, supervised physical exercise in a large cohort of patients with CF. Materials and Methods: Fifty‐nine adult patients with CF that performed regularly supervised physical exercise in the last 3 years in comparison to 59 sex and age matched sedentary patients with CF were included in the study. Results: Physical exercise had significantly beneficial effects on: ( a ) FEV1% decline; ( b ) anthropometric parameters (lower number of cases with altered BMI, waist and arm circumferences); ( c ) lipid and glucose metabolism; ( d ) vitamin D serum levels. Of course, some of this improvement may be because of the better adherence to therapy typical of patients with CF that perform physical activity. Conclusions: Such clinical and metabolic effects make supervised physical activity one of the hubs in managing patients with CF.